The core and hip in soccer athletes compared by gender - Brophy, R. H.; Chiaia, T. A.; Maschi, R.; Dodson, C. C.; Oh, L. S.; Lyman, S.; Allen, A. A.; Williams, R. J. (International Journal of Sports Medicine, 2009)
Gender differences in hip and core strength and range of motion may contribute to the gender based variance in injury risk. This study was designed to test the primary hypothesis that hip and core strength, flexibility and lower extremity dynamic alignment differ in male and female soccer athletes. Ninety-eight collegiate soccer players (54 male, 44 female) participated in this study. Athletes were evaluated for hip range of motion, and hip and abdominal strength. Both male and female soccer players demonstrated limited hip rotation, with less hip internal rotation in males (p<0.0001), and poor abdominal core control, although the males are stronger (p=0.02). Overall hip ROM is shifted towards internal rotation in females compared to males. Female soccer players also have a significant side-to-side disparity in hip abductor strength (p<0.0001), not present in males. The shift in hip ROM towards internal rotation combined with the hip abductor imbalance may be associated with a position of ACL risk with internally rotated hips and valgus knees in female soccer players. Limitations in hip and core strength and range of motion may play a role in the disparity between the male and female rate of ACL injury.